Age and Aesthetics in James Abbott McNeill Whistler’s Arrangement in Grey and Black: Portrait of the Painter’s Mother (1871) - Doley, Caitlin (Age, Culture, Humanities: An Interdisciplinary Journal, 2021)
When one begins looking for them in the visual culture of the nineteenth century, aging and aged bodies crop up in a variety of media, styles, and contexts: in drawings, paintings, and sculptures; in popular history paintings and more obscure aesthetic experiments; in artists’ biographies and critics’ writings. However, the discipline of art history has yet to engage with the master identity that is old age, and practitioners of age studies have yet to truly utilize visual primary sources. This article breaks new scholarly ground by interrogating the relationship between old age and the visual in one of the most famous and best-loved representations of an elderly person in nineteenth-century painting: James Abbott McNeill Whistler’s Arrangement in Grey and Black: Portrait of the Painter’s Mother (1871). The sitter for Whistler’s painting was his then sixty-seven-year-old mother, Anna McNeill Whistler. In this article, I propose that it was Anna’s aged body that caused or, rather, enabled Whistler to have an artistic revelation that was to define his approach to the visual and aesthetics, and propel him to notorious fame.